PERAN BUMDES TATUMI DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DESA KUNEMAN, KECAMATAN ALOR SELATAN, KABUPATEN ALOR - Ritha S. Sarileba; Aris Lambe; Aelsthri Ndandara; Yosep E. Jelahut (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: This study aims to analyze the role of Tattumi Village-Owned Enterprise (BUMDes) in improving the income of the community in Kuneman Village, South Alor District, Alor Regency. This research employed a descriptive qualitative approach involving 12 purposively selected informants consisting of village officials, BUMDes managers, and community members. Data were collected through in-depth interviews, observation, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that BUMDes Tattumi has performed its role through the management of village enterprises, including a village retail store, agricultural and plantation product trading, asset rental services, organic fertilizer production, and educational loan assistance. These business units have improved community access to economic services and supported local economic activities. However, their contribution to increasing community income has not yet been optimal due to limited business development, underutilization of local economic potential, managerial capacity constraints, and limited community participation. The study concludes that BUMDes Tattumi has functioned as a village economic institution, but strengthening institutional governance and developing local potential-based enterprises are necessary to optimize its role in improving community income.Keywords: BUMDes; Role; Community Income; Economic Empowerment; Kuneman Village.